Acupuncture modulates the microbiota-gut-brain axis: a novel therapeutic strategy for amnestic mild cognitive impairment - Xing, Hang; Hu, Wen-long; Bao, Sheng-yong (Frontiers in Neuroscience, 2025)
Amnestic mild cognitive impairment (aMCI) represents a critical prodromal stage of Alzheimer's disease (AD), yet effective therapeutic interventions to prevent or delay this conversion remain an unmet clinical need. Growing evidence implicates dysregulation of the microbiota-gut-brain axis (MGBA)-a complex bidirectional communication network involving neural, immune, and endocrine pathways-in the pathogenesis of neurodegenerative disorders. This perspective proposes that acupuncture, as a multi-target therapeutic approach, may modulate gut microbiota composition and restore MGBA homeostasis, thereby potentially decelerating the progression from aMCI to AD. A systematic understanding of the precise mechanisms through which acupuncture influences the MGBA carries substantial implications for both neuroscience and clinical practice. Future investigations should prioritize the elucidation of these mechanisms and the generation of robust clinical evidence through well-controlled experimental designs.